Building internet capabilities in SMEs - Chapman, P; James-Moore, M; Szczygiel, M; Thompson, D (Emerald, 2000)
Internet based information and communication technology provides the opportunity for small firms to improve their competitiveness. This paper presents a methodology that responds to the needs of small firms whilst overcoming the constraints to their use of these technologies. Key features of this methodology are: provision of a turnkey package of hardware, software, installation and training for Internet connection and operation; identification of opportunities for integrating Internet ICT into business processes that will deliver performance improvement; ongoing IT and business support for a year. The effectiveness of this methodology was examined during its application in 21 SME automotive component suppliers in the West Midlands region of England. This exercise found that 90 per cent of firms continued to use their Internet based ICT capability after a year.